Low-Dose of Bergamot-Derived Polyphenolic Fraction (BPF) Did Not Improve Metabolic Parameters in Second Generation Antipsychotics-Treated Patients: Results from a 60-days Open-Label Study - Bruno, Antonio; Pandolfo, Gianluca; Crucitti, Manuela; Cacciola, Massimo; Santoro, Vincenza; Spina, Edoardo; Zoccali, Rocco A.; Muscatello, Maria R. A. (Frontiers in Pharmacology, 2017)
Objectives: The nutraceutical approach to the management of metabolic syndrome (MetS) might be a promising strategy in the prevention of cardio-metabolic risk. Low-dose bergamot-derived polyphenolic fraction (BPF) has been proven effective in patients with MetS, as demonstrated by a concomitant improvement in lipemic and glycemic profiles. The present study was aimed to further explore, in a sample of subjects receiving second generation antipsychotics (SGAs), the effects on body weight and metabolic parameters of a low dose of BPF (500mg/day) administered for 60 days. Methods: Twenty-eight outpatients treated with SGAs assumed BPF at single daily dose of 500 mg/day for 60 days. Body weight, BMI, fasting levels of glucose, total cholesterol, high density lipoprotein cholesterol, low density lipoprotein cholesterol and triglycerides were determined; moreover, Brief Psychiatric Rating Scale was administered. Results: Low-dose BPF administration did not change clinical and metabolic parameters, as well as clinical symptoms in the study sample. At the end of the trial, among completers (n=24) only nine patients (37.5%) reached an LDL reduction >0 but <50%. Conclusions: Our results demonstrate that patients treated with SGAs may need higher BPF doses for obtaining the positive effects on body weight and metabolic parameters previously found in the general population at lower doses.